Media Dadu Kata Bergambar Pada Muatan Bahasa Indonesia di Sekolah Dasar - Dewi, Ida Ayu Made Martiana; Anak Agung Gede Agung; I Komang Ngurah Wiyasa (Universitas Pendidikan Ganesha, 2022)
The lack of use and existence of innovative and effective learning media impacts the common competency knowledge of Indonesian for third-grade elementary school students. This study aims to describe the visual word dice media design for third-grade students. This research belongs to the type of development research which was developed using the Hannafin and Peck model. The Hannafin and Peck model consist of three development stages: the needs analysis stage, the design stage, and the development and implementation stage. The subjects involved in this study were one design expert, one learning content expert, one instructional design expert, one instructional media expert, three students with high learning outcomes, three with moderate learning outcomes, and three with low learning outcomes. Data collection in the study was carried out using the test method and the questionnaire method. The research instrument used was a questionnaire sheet and 17 objective tests. The data obtained in the study were then analyzed using quantitative descriptive data analysis techniques and inferential statistical analysis using the t-test technique. Based on the results of data analysis, it was found that the feasibility of the media from the results of the expert design test was 90%. They were learning content expert test 97.20%. Learning design expert test 87.50%, learning media expert test 87.50%, and media practicality through individual trials 97.33%. Small group trials 94.89%. The results of the media effectiveness test based on the results of the t-test found that the media was declared effective. Thus, visual dice-based learning media is feasible and effective in learning Indonesian for third-grade students in elementary school.